Akar dan Motif Fundamentalisme Islam:Reformulasi Tipologi Fundamentalisme dan Prospeknya di Indonesia - Nunu Burhanuddin (Wawasan: Jurnal Ilmiah Agama dan Sosial Budaya, 2016)
Political movements and Islamic fundamentalism emerges to respond to internal and external challenges of modernity. Islamic world is also involved in this social upheaval to establish regional strategic meaning in economy and military toward the emerging European countries. In this context, Islamic fundamentalism is understood as the answer of certain social groups and political elites in the Islamic community in term of institutions, concepts and ideals that emerged in modern era. This paper aims to understand the meaning of Islamic fundamentalism in modern context together with its social confrontations, motives, goals and development. This paper shows that there are typology of Islamic fundamentalism in Indonesia, namely: First, fundamentalist group that emerged as a result of the struggles and conflicts of power in Indonesia as well as in The Middle Eastern countriest; second,  fundamentalist group with a closed characteristics, who claimed that their group is right and others are wrong and even blasphemous. In addition, this group denied diversity and aimed of unification. Third, fundamentalist group that gain its influenced in particular Indonesian society like Hizb al-Tahrir of Indonesia.